2016
DOI: 10.1021/acs.jpclett.6b01617
|View full text |Cite
|
Sign up to set email alerts
|

Impact of a Mesoporous Titania–Perovskite Interface on the Performance of Hybrid Organic–Inorganic Perovskite Solar Cells

Abstract: We report on the optimization of the interfacial properties of titania in mesoscopic CH3NH3PbI3 solar cells. Modification of the mesoporous TiO2 film by TiCl4 treatment substantially reduced the surface traps, as is evident from the sharpness of the absorption edge with a significant reduction in Urbach energy (from 320 to 140 meV) determined from photothermal deflection spectroscopy, and led to an order of magnitude enhancement in the bulk electron mobility and corresponding decrease in the transport activati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
86
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 92 publications
(88 citation statements)
references
References 36 publications
(65 reference statements)
2
86
0
Order By: Relevance
“…The average value increases from 0.85 V for the reference device to 1.09 V for the dual modification. This result may be ascribed to the reduction of the electronic disorder at the ETL/perovskite interface . In general, the “electronic disorder” can be interpreted as a measure of the distribution of the electronic density of states (DOS).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The average value increases from 0.85 V for the reference device to 1.09 V for the dual modification. This result may be ascribed to the reduction of the electronic disorder at the ETL/perovskite interface . In general, the “electronic disorder” can be interpreted as a measure of the distribution of the electronic density of states (DOS).…”
Section: Resultsmentioning
confidence: 99%
“…In the past few years, organic–inorganic hybrid halide perovskite materials have come into focus due to their unique optoelectronic properties such as strong visible light absorbance and high carrier mobility . The implementation of this class of materials into solar cells has led to a new generation of rapidly developing photovoltaic technologies.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The full conversion of lead halide into perovskite in the second step is essential to achieve the highest light absorption1617, and we showed that the monovalent cation halide additives ( e.g., NaI and CuBr) result in a complete conversion. Furthermore, the complete coverage of the mesoporous titania layer with the perovskite over-layer is vital to eliminate potential recombination between the hole transport layer ( e.g., Spiro OMETAD) and the electron transport layer ( e.g., mesoporous TiO 2 )23. We illustrated that adding the monovalent cation halides ( e.g., CuI and AgI) can improve the surface coverage of the perovskite capping layer, which leads to a higher open circuit voltage for the device.…”
Section: Discussionmentioning
confidence: 99%
“…Over the last decades mesoporous titania has gained considerable research interest for applications in catalysis, photovoltaics, and rechargeable lithium‐ion batteries . The great success is closely related to its superior chemical stability, large surface‐to‐volume ratio, tunable pore size, and having a wide bandgap .…”
mentioning
confidence: 99%